2018
DOI: 10.1017/jfm.2018.819
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of high-speed boundary-layer stability to base-flow distortion

Abstract: The linear stability of high-speed boundary layers can be altered by distortions to the base velocity and temperature profiles. An analytic expression for the sensitivity is derived for parallel and spatially developing boundary layers, the latter using linear parabolized stability equations and their adjoint. Both the slow mode, S, and the fast mode, F, are investigated at Mach number 4.5. The mode S is more sensitive with respect to distortion in base velocity than in base temperature. The sensitivity is lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 79 publications
4
20
0
Order By: Relevance
“…These observations are consistent with the notion that the synchronization point of instability waves is a key modulator of stability in thermally treated boundary layers (Zhao et al. 2018; Park & Zaki 2019).
Figure 4. Surface heat flux of the optimized solution after the final iteration in physical space, amplitudes of heat flux complex coefficients of the optimized solution in spectral space and surface heat flux of the reduced heat flux case in physical space.
…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These observations are consistent with the notion that the synchronization point of instability waves is a key modulator of stability in thermally treated boundary layers (Zhao et al. 2018; Park & Zaki 2019).
Figure 4. Surface heat flux of the optimized solution after the final iteration in physical space, amplitudes of heat flux complex coefficients of the optimized solution in spectral space and surface heat flux of the reduced heat flux case in physical space.
…”
Section: Resultssupporting
confidence: 91%
“…The spatial growth rates, streamwise wavenumbers and phase speeds of modes and at those frequencies are plotted as a function of Reynolds number in figure 5. The figure is evaluated using parallel linear theory, and shows the typical characteristics of slow and fast modes (Fedorov 2011; Fedorov & Tumin 2011; Park & Zaki 2019): (i) at low Reynolds number modes and appear, respectively, near the slow acoustic, , and fast acoustic, , branches of the spectrum; (ii) the former accelerates and the later decelerates with Reynolds number until they synchronize; and (iii) the profiles of mode show a discontinuity at the location where its phase speed approaches from either side which corresponds to crossing the continuous branch of entropy and vorticity modes. The synchronization Reynolds numbers for is at and for it is .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to highlight the importance of the present nonlinear approach in determining the inflow disturbance spectrum, we examine other possible inflow conditions that are selected based on linear theory alone. The starting point is to evaluate the linear evolution of all the Orr–Sommerfeld and Squire instability waves that are part of the inlet condition, using the linear parabolized instability equations (Park & Zaki 2019). The -factor associated with every wave was obtained as follows: where is the energy of the mode at the inlet.…”
Section: Resultsmentioning
confidence: 99%
“…Lysenko & Maslov (1984) explained the deviations in measured and theoretical instability growth rates in cooled flows, in part, in terms of the angle of waves infiltrating the boundary layer. Park & Zaki (2019) performed adjoint sensitivity analyses that detail how uncertainty in mean-velocity and temperature profiles affect growth rates; they showed that the measured growth rates by Lysenko & Maslov (1984) can result from 1 to 2 % uncertainty in wall temperature.…”
Section: Introductionmentioning
confidence: 99%